Funcionamento executivo em pacientes com esquizofrenia refratária - Vicente, Marcella de Oliveira [UNIFESP] (2016)
Background: Treatment resistance affects up to one third of patients with schizophrenia. Cognitive deficits, especially executive ones, have been considered core features of the illness. The nature of such deficits in treatment-resistant subjects, however, is still unknown. The main aim of present study was to evaluate specific components of executive functioning in treatment-resistant schizophrenia subjects (TRS), comparing with schizophrenia subjects without history of resistance to treatment (Non-TRS) and healthy subjects. Methodology: 65 TRS patients (adapted IPAP criteria), 60 NonTRS patients, and 112 healthy controls were examined. Subjects were tested with a comprehensive and computerized battery of cognitive tests, including measures to assess three specific executive components, namely updating, shifting and inhibition. Results: Schizophrenia subjects performed poorly on general executive functioning, updating and inhibition tasks in comparison to healthy controls. The global measure (TOL) could not differentiate TRS from NonTRS patients. Among the three executive dimensions, TRS subjects performed worse than NonTRS only in updating of working memory function. Conclusion: Present findings suggest a more severe executive dysfunction in TRS as compared to NonTRS subjects, particularly affecting updating of working memory function. In addition, results support the hypothesis that TRS is a more severe stage or a more severe subtype of schizophrenia. Future longitudinal studies examining first-episode schizophrenia subjects may be particularly elucidative to determine whether patients who develop TRS already present such deficits at the disease onset.